2023
DOI: 10.21203/rs.3.rs-2539372/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasmodium ARK2-EB1 axis drives the unconventional spindle dynamics, scaffold formation and chromosome segregation of sexual transmission stages

Abstract: Mechanisms of cell division are remarkably diverse, suggesting the underlying molecular networks among eukaryotes differ extensively. The Aurora family of kinases orchestrates the process of chromosome segregation and cytokinesis during cell division through precise spatiotemporal regulation of their catalytic activities by distinct scaffolds. Plasmodium spp., the causative agents of malaria, are unicellular eukaryotes that have three divergent aurora-related kinases (ARKs) and lack most canonical scaffolds/ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 61 publications
(80 reference statements)
2
28
0
Order By: Relevance
“…In contrast, deletion of EB1 in P. falciparum and P. yoelli leads to the formation of gametes that were entirely deficient of DNA and incapable of fertilising females, highlighting interesting species-specific differences in DNA segregation in male gametocytes (32,47). A paternal phenotype followed by an early oocyst arrest has also been described for other Plasmodium parasite lines lacking proteins such as the formin-like protein MISFIT (49), the microtubule motor kinesin-8X (50), the aurora kinase Ark2 (48), and for a parasite line that expresses actin 1 in place of actin 2 (44). While their precise connection to the Arp2/3 complex or Arp2/3mediated actin polymerization remains to be determined, a unifying feature of these paternal defects is that they do not affect ookinete development but arrest parasites only in the oocyst stage.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, deletion of EB1 in P. falciparum and P. yoelli leads to the formation of gametes that were entirely deficient of DNA and incapable of fertilising females, highlighting interesting species-specific differences in DNA segregation in male gametocytes (32,47). A paternal phenotype followed by an early oocyst arrest has also been described for other Plasmodium parasite lines lacking proteins such as the formin-like protein MISFIT (49), the microtubule motor kinesin-8X (50), the aurora kinase Ark2 (48), and for a parasite line that expresses actin 1 in place of actin 2 (44). While their precise connection to the Arp2/3 complex or Arp2/3mediated actin polymerization remains to be determined, a unifying feature of these paternal defects is that they do not affect ookinete development but arrest parasites only in the oocyst stage.…”
Section: Discussionmentioning
confidence: 89%
“…A core protein connecting the kinetochores to the spindle during male gametogenesis is end-binding protein 1 (EB1) ( 32 , 47 , 48 ). Deletion of EB1 in P. berghei resembles the phenotype of ARPC1(-), with an arrest in a delayed-death like manner in early oocysts ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During male gametogenesis, this pattern was even clearer: the number and location of the NEK1 foci correlated with the ploidy of the parasite, and the splitting of the MTOC was observed associated with NEK1 foci at the different mitotic stages during genome replication from 1N to 8N (Fig 2A). The localisation of NEK1 in real time relative to a number of markers for kinetochores (NDC80) (Zeeshan et al, 2020), microtubules (EB1), spindle kinase (ARK2)(Zeeshan et al, 2023), and axoneme marker (Kinesin 8B) (Zeeshan et al, 2019a), showed that NEK1 is part of the outer MTOC in the cytoplasmic compartment. This was confirmed by expansion microscopy and super resolution microscopy using various centrosome and spindle markers, including centrin, γ-tubulin and α-tubulin.…”
Section: Discussionmentioning
confidence: 99%